2016
DOI: 10.1371/journal.ppat.1005831
|View full text |Cite
|
Sign up to set email alerts
|

Placental Sequestration of Plasmodium falciparum Malaria Parasites Is Mediated by the Interaction Between VAR2CSA and Chondroitin Sulfate A on Syndecan-1

Abstract: During placental malaria, Plasmodium falciparum infected erythrocytes sequester in the placenta, causing health problems for both the mother and fetus. The specific adherence is mediated by the VAR2CSA protein, which binds to placental chondroitin sulfate (CS) on chondroitin sulfate proteoglycans (CSPGs) in the placental syncytium. However, the identity of the CSPG core protein and the cellular impact of the interaction have remain elusive. In this study we identified the specific CSPG core protein to which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 68 publications
2
78
1
4
Order By: Relevance
“…When infected RBCs from infected placentas were incubated with uninfected term placentas, the cells bound only in the periphery of the intervillous space (Fried & Duffy, ) indicating a difference been infected and uninfected placentas. However, in a subsequent study using placental‐type infected RBCs (i.e., expressing VAR2CSA), intervillous mesh was observed in the placentas from healthy women although the mesh was not as dense as seen with infected placentas (Ayres Pereira et al, ).…”
Section: Role Of Fibrin In the Accumulation Of Infected Rbcs In The Imentioning
confidence: 93%
See 2 more Smart Citations
“…When infected RBCs from infected placentas were incubated with uninfected term placentas, the cells bound only in the periphery of the intervillous space (Fried & Duffy, ) indicating a difference been infected and uninfected placentas. However, in a subsequent study using placental‐type infected RBCs (i.e., expressing VAR2CSA), intervillous mesh was observed in the placentas from healthy women although the mesh was not as dense as seen with infected placentas (Ayres Pereira et al, ).…”
Section: Role Of Fibrin In the Accumulation Of Infected Rbcs In The Imentioning
confidence: 93%
“…More recently, it was shown in an ex vivo model of perfused placental tissue that soluble chondroitin sulfate A and specific antibodies directed against VAR2CSA inhibited the binding of infected RBCs (Pehrson et al, ). Also, it was found that soluble chondroitin sulfate A inhibited the binding of the recombinant VAR2CSA receptor to both the syncytiotrophoblast and the intervillous mesh in tissue sections of term placentas (Ayres Pereira et al, ). The same authors reported that an antibody to chondroitin sulfate (CS‐56), which binds to both chondroitin sulfate A and chondroitin sulfate C, bound in placental tissue sections to both the syncytiotrophoblast and the intervillous mesh with a pattern similar to that of VAR2CSA as well as the truncated active portion of recombinant VAR2CSA previously reported on by Clausen et al () (referred to in Ayres Pereira et al (), as rVAR2).…”
Section: Role Of Chondroitin Sulfate Proteoglycans In Placental Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…y por ende no desarrolla una inmunidad efectiva en comparación con las multigestantes 24 , además, la concentración de hormonas sexuales y el cortisol, tienden a disminuir a medida que aumenta la paridad 10,19,18 Fisiopatología de malaria placentaria Los eritrocitos infectados por Plasmodium spp., expresan un antígeno variante en su membrana, denominado -Plasmodium falciparum erythrocyte membrane protein 1-(PfEMP1) 25 , que facilita la adhesión de las células infectadas a receptores de condroitín sulfato A (CSA), presentes en la placenta 26 ; esta unión facilita el ingreso y secuestro del patógeno en el espacio intervelloso 27 , allí se desencadena una respuesta inmune pro-inflamatoria, mediada inicialmente por la liberación de TNF-α por parte de las células natural killer uterinas (NKu), que tiene un efecto químioatrayente sobre monocitos y macrófagos para amplificar la respuesta inmunitaria TH1 , en un intento por defender el contexto placentario contra la infección 19 .…”
Section: Malaria Y Paridadunclassified
“…Recientemente se ha descritola presencia de alteraciones cardiovasculares y neurológicas una vez se ha superado la etapa neonatal e incluso en la vida adulta, la hipertensión, diabetes y síndrome metabólico son los problemas cardiovasculares asociados a la RCIU; por otro lado, los trastornos neurológicos se han relacionado con un menor coeficiente intelectual, pobre rendimiento académico y problemas de comportamiento 26,36 . Se resalta que su pronóstico neurológico es peor mientras más temprano se haga el diagnóstico prenatal de RCIU y cuando se evidencia disminución o ausencia del flujo al final de la diástole en el Doppler de arteria umbilical 40 .…”
Section: Consecuencias De La Rciuunclassified